KUALITAS PELAYANAN ADMINISTRASI DESA - Adam, Sitti Noer Fadhillah; Aneta, Asna; Abdussamad, Juriko (Jambura Journal of Administration and Public Service, 2025)
This study aims to analyze the quality of village administrative services in Bulango Selatan District, Bone Bolango Regency, based on the five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document studies in three selected villages: Ayula Selatan, Huntu Selatan, and Lamahu. The findings indicate that physical facilities for service delivery remain limited, with insufficient technological devices and cramped waiting areas, affecting comfort and service efficiency. Reliability is suboptimal due to delays in document processing and procedural inconsistencies. While village officials demonstrate good personal responsiveness, it is not supported by adequate service information systems. The assurance dimension faces challenges in safeguarding citizen data, as manual archiving remains vulnerable. Empathy among officials is high, evident in their flexibility to serve vulnerable groups, though this has yet to be formalized in policy. The study recommends strengthening physical facilities, drafting written SOPs, digitizing archives, providing informational media, and training officials in public service ethics. These efforts are expected to foster a more professional, inclusive, and responsive village administrative service system that aligns with community needs. Penelitian ini bertujuan untuk menganalisis kualitas pelayanan administrasi desa di Kecamatan Bulango Selatan, Kabupaten Bone Bolango, berdasarkan lima dimensi SERVQUAL: Bukti Fisik (Tangibles), Keandalan (Reliability), Daya Tanggap (Responsiveness), Jaminan (Assurance), dan Empati (Empathy). Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi pada tiga desa terpilih: Ayula Selatan, Huntu Selatan, dan Lamahu. Hasil penelitian menunjukkan bahwa fasilitas fisik pelayanan masih terbatas, dengan minimnya perangkat teknologi dan ruang tunggu yang sempit, sehingga menghambat kenyamanan dan efisiensi pelayanan. Keandalan pelayanan belum optimal karena keterlambatan penyelesaian dokumen dan ketidakkonsistenan prosedur. Responsivitas aparatur desa cukup baik secara personal, namun belum didukung sistem informasi pelayanan yang memadai. Dimensi jaminan menghadapi kendala pada keamanan data warga akibat arsip manual yang rentan. Sementara itu, empati aparatur tinggi, terlihat dari fleksibilitas mereka dalam melayani kelompok rentan, meskipun belum diatur dalam kebijakan formal. Penelitian merekomendasikan penguatan fasilitas fisik, penyusunan SOP tertulis, digitalisasi arsip, penyediaan media informasi, dan pelatihan aparatur berbasis etika pelayanan publik. Dengan demikian, diharapkan dapat tercipta pelayanan administrasi desa yang lebih profesional, inklusif, dan responsif terhadap kebutuhan masyarakat.